2012
DOI: 10.2174/1874347101206010080
|View full text |Cite
|
Sign up to set email alerts
|

Automated Voxel-Wise Brain DTI Analysis of Fitness and Aging

Abstract: Diffusion Tensor Imaging (DTI) has become a widely used MR modality to investigate white matter integrity in the brain. This paper presents the application of an automated method for voxel-wise group comparisons of DTI images in a study of fitness and aging. The automated processing method consists of 3 steps: 1) preprocessing including image format converting, image quality control, eddy-current and motion artifact correction, skull stripping and tensor image estimation, 2) study-specific unbiased DTI atlas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Seven studies examined WM microstructure cross-sectionally. Of seven studies that examined FA, three studies reported that higher levels of PFA were associated with increased FA: within the corpus callosum ( Johnson et al, 2012 ), superior longitudinal fasciculus and arcuate fasciculus ( Liu et al, 2012 ), and superior longitudinal fasciculus, superior corona radiate, inferior fronto-occipital fasciculus and inferior longitudinal fasciculus ( Tseng et al, 2013a ). Of three studies that examined MD, findings were not significant for two studies ( Johnson et al, 2012 , Marks et al, 2011 ), while Tseng et al (2013a) reported decreases in MD in non-overlapping regions to their FA results, within the cingulum and posterior thalamic radiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies examined WM microstructure cross-sectionally. Of seven studies that examined FA, three studies reported that higher levels of PFA were associated with increased FA: within the corpus callosum ( Johnson et al, 2012 ), superior longitudinal fasciculus and arcuate fasciculus ( Liu et al, 2012 ), and superior longitudinal fasciculus, superior corona radiate, inferior fronto-occipital fasciculus and inferior longitudinal fasciculus ( Tseng et al, 2013a ). Of three studies that examined MD, findings were not significant for two studies ( Johnson et al, 2012 , Marks et al, 2011 ), while Tseng et al (2013a) reported decreases in MD in non-overlapping regions to their FA results, within the cingulum and posterior thalamic radiation.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, preference was first given to the study with the largest sample size ( Tian et al, 2014a preferred to Tian et al, 2014b ). Where sample size was equal, preference was given to analyses of a global measure of WM volume expressed as a percentage of intracranial volume (ICV), rather than raw values ( Tseng et al, 2013b preferred to Tseng et al, 2013a ), and voxel-wise analysis was preferred to region-of-interest (ROI) analysis ( Liu et al, 2012 preferred to Marks et al, 2011 ). When studies reported multiple MRI analysis methods in a single paper (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent review found mixed results (Sexton et al, 2016) on cross-sectional associations between PA and WMM. Increased fractional anisotropy (FA) with higher levels of PF has been shown within the corpus-callosum (Johnson et al, 2012), superior longitudinal fasciculus and arcuate fasciculus (Liu et al, 2012), and superior/inferior longitudinal fasciculus, superior corona radiate (Tseng et al, 2013). In the studies that examined mean diffusivity (MD), two studies (Marks et al, 2011;Johnson et al, 2012) reported no significant finding.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies now focuses on the investigation of the effects of PA on white matter properties (Sexton et al, 2016). In addition to repeated findings of an association between PA and white matter volume as well as white matter lesions (Sexton et al, 2016), many studies reported a positive effect of PA on WMI (Gow et al, 2012;Johnson et al, 2012;Liu et al, 2012;Tseng et al, 2013a). PA thus qualifies as a promising tool to counteract the age-related decline in WMI and to preserve cognition functioning via the association with WMI.…”
Section: Introductionmentioning
confidence: 99%